THE CONTENT OF CAESIUM-137 IN THE RIVERSIDE AND WATER VEGETATION VETKA AND CHECHERSK DISTRICTS OF THE GOMEL REGION OF BELARUS - N. M. Dajneko; S. F. Timofeev (Радиационная гигиена)
The content of radiocaesium was studied in 58 plant samples in 2 districts with only 12 (20,6%) exceeding the allowable level which equals 370 Bk/kg. In Vetka district the highest specific activity of caesium-137 (Bk/kg) was demonstrated by Equisetum arvense and Comarum palustre among the medium-sized euhydrophytes in  the  second  object,  which  3,7  and  5,2  times  exceeds  the  standard.   Ceratophyllum  demersum  has  the  highest accumulation coefficient. In Chechesk district medium-sized euhydrophytes Juncus effusus and Sium latifolium in the second object exceed the standard 7,8–2,2 times. Stratiotes aloides demonstrates the highest accumulation coefficient.